The Synthesis of 2,5-Dioxaspiro[3.4]octane Building Blocks: Three-Dimensional Spirocyclic Analogs of 1,4-Dioxanes - Bohdan V. Vashchenko; Eduard V. Litskan (Журнал органічної та фармацевтичної хімії)
A ring-closing metathesis (RCM) strategy was employed for the synthesis of spirooxetane compounds with a tetrahydrofuran (THF) core. The approach proposed relied on the preparation of an unsaturated spirooxetane from vinyl oxetanol. The reaction sequence involved the NaH-mediated О-alkylation with methyl 2-(bromomethyl)acrylate in the presence of TBAI. The subsequent RCM reaction using the Grubbs’ II catalyst gave the dihydrofuran carboxylate with a yield of 70 %. The hydrogenation under high-pressure conditions using a Pearlman’s catalyst made it possible to obtain the saturated THF-derived carboxylate, which was then subjected to alkaline hydrolysis to give a stable lithium carboxylate. The corresponding alcohol obtained via LiAlH4-mediated reduction of the ester was oxidized to the corresponding aldehyde using DMP. The alcohol was further converted into a mesylate serving as a precursor for the corresponding amine and bromide. The set of dioxane analogs proposed can serve as promising building blocks readily available on a multigram scale for the scientific community.